On the way to building an integrated computational environment for the study of developmental patterns and genetic diseases - Turinsky, Andrei L (Dove Medical Press, 2006)
Genetic diseases and developmental patterns should be studied on several levels: from macroscale (organs and tissues) to nanoscale (cells, genes, proteins). Due to the overwhelming complexity of the life science data, it is common that disparate data pieces are meticulously stored but never fully analyzed or correlated. We have begun to develop a novel methodology based on virtual reality techniques for the study of these phenomena. Our key approach to knowledge integration is a top-down mapping of data onto visual contexts. For each organism that we want to study, a structural model is created and used as a visual “wireframe” onto which other data types are superimposed in a top-down assembly. Data analysis tools, visual controls, and queries are enabled so that users can interactively explore data. Our visualization technology gives users an opportunity to map disparate data onto a common model, and search visually for hitherto unknown patterns and correlations contained within the data. It is our goal to eventually transform genomics research from measuring various data pieces analytically into a fully interactive exploration of combined data in a 4D immersive visual environment that best matches a researcher’s intuition.